Analyzing and conferring with students on running records to improve reading outcomes - Sandager, Brigid (My University, 2014)
The purpose of this action research was to show changes in student reading outcomes with the use of individual assessments. Running records provide the teacher with knowledge about individual students' reading strengths and needs. The analysis of running records provides data to use when conferring with students to help determine number of miscues and types of miscues made during oral reading. The first part of the study was the use of running records for miscue analysis. By analyzing the types of miscues a teacher can assess a student's reading comprehension. The second component, conferring was used to collect data from students and than provide feedback. The use of analysis and conferring brought about a change in student reading outcomes. Students were able to take ownership in their literacy growth. They determined what skills and strategies they had used effectively while reading and what skills and strategies need to be strengthened to meet their individual literacy goals.
Plan B Paper. 2014. Master of Science in Education- Reading--University of Wisconsin-River Falls. Teacher Education Department. 34 leaves. Includes bibliographical references (leaves 26-28).
Keywords: Reading comprehension--Evaluation; Reading comprehension--Study and teaching (Elementary)--Minnesota; Reading (Elementary)--Evaluation